The Influence of Leadership Style & Environment on Employee Performance With Work Motivation as a Mediation Variable PT. Unilab Perdana - Famdan, Famdan; Hartono, Arif (Journal Research of Social Science, Economics, and Management, 2022)
The title of this research is the analysis of the influence of leadership style (LS) and work environment (WE) on employee performance (EP) with work motivation (WM) as a mediating variable at PT. Prime Unilab. This study aims to determine the mediating effect of work motivation in the relationship between leadership style and work environment on employee performance. This research was conducted quantitatively and used a questionnaire as a data collection method. The population is 300 employees. The research sample used was 172 employees. Therefore, sampling is simple and multiple linear regression analysis and path analysis. The results of this study indicate that leadership style and work environment have a positive and significant influence on employee performance, leadership style and work environment have a positive and significant influence on work motivation. Work motivation can mediate the relationship between leadership style and work environment on employee performance.